2010
DOI: 10.1007/s10661-010-1662-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of the road dusts from two parks in Wuhan city, China: implications for mapping urban environment

Abstract: Magnetic parameters and heavy metal concentrations of road dusts collected from two parks with distance about 16 km in Wuhan city, China, were measured. The Guishan Park is circled by main roads with heavy traffic, and the Moshan Park is located on the downwind hills of steelworks and a power plant. Mean values of magnetic susceptibility (χ) and saturation magnetization (M (s)) of the dusts from the Moshan Park are 1.31 and 1.57 times those from the Guishan Park, respectively. Their magnetic mineralogy is domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Wuhan is the largest metropolis in central China, with fast economic growth, high population density, abundant water resources, strong industrial foundation, and highly developed transportation network. Although several studies about trace metals in soil in this city have been done, most of them were restricted to small specific areas (Qu et al 2013;Yang et al 2011) or water bodies (Jiang et al 2014;Liu et al 2008;Yang et al 2009Yang et al , 2010. For example, Qu et al (2014) recently studied the trace metal contamination status in the Wuhan Donghu High-tech Development Park and assessed the potential ecological risk of trace metals in soil to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Wuhan is the largest metropolis in central China, with fast economic growth, high population density, abundant water resources, strong industrial foundation, and highly developed transportation network. Although several studies about trace metals in soil in this city have been done, most of them were restricted to small specific areas (Qu et al 2013;Yang et al 2011) or water bodies (Jiang et al 2014;Liu et al 2008;Yang et al 2009Yang et al , 2010. For example, Qu et al (2014) recently studied the trace metal contamination status in the Wuhan Donghu High-tech Development Park and assessed the potential ecological risk of trace metals in soil to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between heavy metals can reflect their sources and pathways (Yang et al, 2011;Lu et al, 2017a). Pearson correlation analysis results are shown in Table 2.…”
Section: Source Identificationmentioning
confidence: 99%
“…The Cu content of road dust may come from engine and brake wear, as well as mechanical abrasion of vehicle parts, while Zn mainly originates from lubricating oil and attrition of automobile tires (Dehghani et al, 2017). Historically, Pb has been an important gasoline additive and although China banned the addition of Pb to gasoline since the early 2000's, Pb has a long half-life and a low leaching rate, leading to its accumulation in urban environments over time (Yang et al, 2011). It has also been reported that Cu, Pb, and Zn are related to industrial activities as they can be released during metal processing and smelting (Dietrich et al, 2018).…”
Section: Source Identificationmentioning
confidence: 99%
“…Gracias a su uso, estos métodos han revelado que las concentraciones de MP en el SV de áreas alrededor de autopistas, industrias, comercios y zonas mixtas presentan elevadas concentraciones, afectando probablemente a los usuarios y residentes de estas zonas [13]- [15]. Existen también otros métodos tales como el grado de contaminación (Cdeg) y el índice de carga multielemento (PLI), que se han utilizado frecuentemente para evaluar de manera integral la contaminación a partir de todos los MP asociados con el SV [16], [17].…”
Section: Introductionunclassified